Modernity, frontiers and revolutions : proceedings of the 4th International Multidisciplinary Congress (PHI 2018), 3-6 October 2018, S. Miguel, Azores, Portugal /: proceedings of the 4th International Multidisciplinary Congress (PHI 2018), 3-6 October 2018, S. Miguel, Azores, Portugal. (2019) - Unknown
No abstract available